The Franciscan and the Jesuit: traditions of Brazilian education - Luiz Fernando Conde Sangenis (Universidade Federal do Rio Grande do Sul, 2018)
The Franciscan and the Jesuit are Western cultural traditions born in Europe and expanded to throughout the world. We have approached the circumstances of this presence in America and Brazil. Here they are designed in the manner of ideal types in dialogue, which composed a creative tension within our educational history. We wish to highlight the Franciscan tradition that remains sidelined by researchers and authors, even in the basic texts for the decipherment of Brazil. To understand the Franciscan and the Jesuit, and from the imbrication of the theme with the field of colonial education, we used paradigmatic texts and authors of both traditions, particularly Gilberto Freyre and Fernando de Azevedo.